Eksplorasi Kemampuan Berhitung Sederhana dengan Pendekatan Permainan Kolam Mini Pada Anak Usia Dini - Nuzla Aimmatu Rasyida; Uun Hasunah; Siti Inganah (UIN Fatmawati Sukarno Bengkulu, 2026)
This study explores early childhood simple numeracy skills through a “mini pool” play activity themed Allah’s creatures, focusing on land and water animals. A qualitative descriptive approach was applied to describe the learning process using media such as water animal toys inside and land animal outside a container. Data were collected through observation, tinterview, and documentation. The findings reveal that the activity effectively supports children’s understanding of basic addition and subtraction in a concrete manner. Children employed various counting strategies, including one-to-one counting, subitizing, and object grouping. Their emotional engagement and social interaction were positive, showing enthusiasm and natural mathematical communication. Teacher facilitation played an important role in guiding children’s thinking. This study confirms that contextual play-based learning is beneficial for early numeracy development and suggests further variation and teacher support to optimize outcomes.